Analysis of the phenolic composition of fungus‐resistant grape varieties cultivated in Italy and Germany using UHPLC‐MS/MS†. (10th September 2014) - Ehrhardt, Carolin; Arapitsas, Panagiotis; Stefanini, Marco; Flick, Gerhard; Mattivi, Fulvio; Giorgi, Gianluca
<x xml:space="preserve">Abstract</x> The phenolic composition of grape berries grown in Italy (Cabernet Cortis, Johanniter, Solaris, Phoenix, and Regent) and in Germany (Regent and Phoenix) was analyzed using two complementary LC‐MS/MS (Liquid Chromatography ‐ Tandem Quadrupole Mass Spectrometry) methods. These five cultivars belong to fungus‐resistant grape varieties (PIWI) and little is known about their phenolic profile, although phenolics such as phytoalexins have been recognized, playing a key role in the resistance mechanism. A triple quadruple mass spectrometer detector was used for both identification and quantification, and analytical tools from untargeted metabolomics were applied to check and control the quality of the results. Specifically, biological, technical, and instrumental replications were included in order to study the variability at different levels. The results allowed tuning of the sampling protocol and provided a rich phenolic metabolite profile for the aforementioned PIWI varieties, as compared with Vitis vinifera cultivars, especially in the class of stilbenes. Copyright © 2014 John Wiley & Sons, Ltd.